ATRT-07. HIGH-DOSE CHEMOTHERAPY AND AUTOLOGOUS STEM CELL TRANSPLANTATION FOR AN ADULT PRESENTATION OF THE ATYPICAL TERATOID-RHABDOID TUMOR (ATRT). (4th December 2020) - Mrugala, Maciej; Raghunathan, Aditya; Leis, Jose
Abstract: BACKGROUND: ATRT is a rare primary CNS tumor occurring predominantly in children with the peak age of onset at less than 3 years old. Adult presentations are exceedingly rare, associated with poor prognosis and no standard therapies exist. METHODS: Case presentation. RESULTS: 61 y old woman presented with headaches, sinus pressure, and cognitive decline. She was found to have a pineal tumor causing obstructive hydrocephalus. The patient underwent gross total resection of the tumor with pathology reported as ATRT. Her CNS staging, including CSF, was negative. She subsequently received radiotherapy to the resection bed. There was no consensus on what should be the next step in her therapy given lack of data in adults. Ultimately, we adopted a pediatric regimen and treated the patient with a combination of high-dose chemotherapy with cisplatin, cyclophosphamide, and vincristine followed by autologous stem cell transplantation (ASCT). This regimen called for up to 4 cycles of chemotherapy with ASCT and we had collected enough cells to complete 3 cycles. The patient completed 2 cycles of therapy with moderate toxicity. Her CNS imaging remained stable with no evidence of recurrence 14-months from the original diagnosis. CONCLUSIONS: ATRT continues to be an exceedingly rare diagnosis in adults. No standard therapies exist and treatment decisions are challenging given lack of data and lack of prospective clinical trials. Pediatric regimens can frequently be adopted for adults although high-dose chemotherapy with ASCT can be challenging. Our case exemplifies the feasibility of treating ATRT in an adult in the most aggressive fashion.